2007
DOI: 10.1186/1471-2148-7-215
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear OXPHOS genes in insecta: a common evolutionary origin, a common cis-regulatory motif, a common destiny for gene duplicates

Abstract: Background: When orthologous sequences from species distributed throughout an optimal range of divergence times are available, comparative genomics is a powerful tool to address problems such as the identification of the forces that shape gene structure during evolution, although the functional constraints involved may vary in different genes and lineages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…Enzymes and structural components of the mitochondria are synthesized mainly from the nuclear genome. Mitochondrial enzymes frequently contain duplicates with testis-biased expression patterns for one of them, based on microarray analysis of Drosophila males and females [ 4 , 5 ]. Spermatid mitochondria aggregate, fuse and form the Nebenkern in round spermatids [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes and structural components of the mitochondria are synthesized mainly from the nuclear genome. Mitochondrial enzymes frequently contain duplicates with testis-biased expression patterns for one of them, based on microarray analysis of Drosophila males and females [ 4 , 5 ]. Spermatid mitochondria aggregate, fuse and form the Nebenkern in round spermatids [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…OXPHOS and CRP genes. B. mori and D. melanogaster OXPHOS and CRP protein sequences were retrieved (Marygold SJ et al, 2007;Porcelli D et al, 2007) and…”
Section: Genome Assemblymentioning
confidence: 99%
“…All 79 ribosomal proteins conserved between mammals and D. melanogaster (Yoshihama M et al, 2002;Marygold SJ et al, 2007) have orthologs in T. ni, further evidence of the completeness of the genome assembly (Supplementary file 1B). Finally, a search for genes in the highly conserved nuclear oxidative phosphorylation (OXPHOS) pathway (Porcelli D et al, 2007) uncovered T. ni orthologs for all known D. melanogaster OXPHOS genes (Supplementary file 1C).…”
mentioning
confidence: 99%
“…Furthermore, a first in silico analysis of D. melanogaster ’s nuclear energy gene sequences has suggested that a single regulatory element, resulting in a genetic regulatory circuit, can coordinate the expression of the whole set of energy-producing genes in this insect [ 28 , 29 ]. This motif is known as Nuclear Respiratory Gene (NRG) element [ 28 , 30 ]. It is a palindromic 8-bp sequence (TTAYRTAA) shared by all the nuclear insect oxidative phosphorylation (OXPHOS) genes, as well as by many other nuclear genes involved in mitochondrial biogenesis and function [ 28 , 30 ].…”
Section: Introductionmentioning
confidence: 99%